Implikasi Perpanjangan Masa Jabatan Presiden 3 Periode di Indonesia - Sarifa Rosita; Siti Fatimah (Bulletin of Community Engagement, 2024)
Indonesia is a country whose government system is a presidential system of government, as stated in article 4 of the 1945 Constitution of the Republic of Indonesia, the President serves as head of State as well as head of Government. The proposal to extend the presidential term of office received pros and cons reactions from the public and the first proposal emerged so that the elected president could carry out the development program completely. The type of research in this research is library research, this type of research is research using literature (libraries) in the form of notebooks or reports of research results from previous research. The results of this research are, The implications arising from the extension of the presidential term of office for 3 terms are a social and political crisis for the second time, the emergence of authoritarian government power and allowing the practice of corruption, collusion and nepotism, demonstrators carried out by students and several academics and political figures who stated that the proposal was something that did not reflect democratic principles.